Influence of Social Media on Adolescent Mental Health: A Gendered Perspective - Arif, Aynee; Manzoor, Shazia; Rashid, Javaid (Indian Journal of Educational Technology, 2025)
This study attempts to understand the relationship between Social Media (SM) usage and Adolescent Mental Health (AMH) with a focus on the gendered coping mechanisms employed by adolescents to mitigate the negative impacts of excessive digital engagement. The objective is to examine the literature and evidence available as to how adolescent boys and girls develop distinct strategies to manage SM addiction and its associated stressors. Using a systematic literature review and thematic analysis of empirical studies, this research identifies key patterns in coping mechanisms and support systems. Findings indicate that adolescent boys predominantly adopt problemfocused strategies, such as seeking solutions or engaging in physical activities, while girls tend toward emotion-focused coping, including seeking emotional support and selfsoothing practices. The study also highlights the influence of peer and family networks in shaping coping behaviours. However, a critical gap persists in empirical research concerning adolescents’ perceptions of SM and how these coping strategies evolve over time and across diverse socio-economic and cultural contexts. The study emphasizes the need for longitudinal, culturally sensitive research to deepen our understanding of these dynamics. It concludes by advocating for tailored, gender-responsive interventions to support mental health in adolescents in the technological age, addressing both the risks and potential aspects of SM use.